A multi-objective analysis of a rural road network problem in the hilly regions of Nepal - Shrestha, Jagat Kumar
This paper considers the rural road network upgrading problem, using a multi-objective optimization model, to support decision-makers in the choice of roads to upgrade in the hilly regions of Nepal. The model considers two objectives: minimization of user operation costs and maximization of population covered. The problem was solved for a real-world rural road network in the Gorkha district of Nepal. For this case, all non-dominated solutions were obtained and the ones providing more interesting trade-offs were analysed. The model was found suitable for the case under study, and possibly, easily extendable to rural areas of other developing countries.